2016
DOI: 10.1002/ptr.5641
|View full text |Cite
|
Sign up to set email alerts
|

The Prokinetic, Laxative, and Antidiarrheal Effects of Morus nigra: Possible Muscarinic, Ca2+ Channel Blocking, and Antimuscarinic Mechanisms

Abstract: Morus nigra Linn. (black mulberry) is used in gastrointestinal ailments. This study demonstrates gut modulatory properties of M. nigra. The prokinetic, laxative, and antidiarrheal activities of M. nigra were assessed in mice, while isolated rabbit jejunum and guinea-pig ileum were used to explore insight into mechanism(s). At 30 and 70 mg/kg, the crude extract of M. nigra (Mn.Cr) exhibited atropine-sensitive prokinetic and laxative effects, similar to carbachol (CCh). While at higher doses (100, 300, and 500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Almost all the parts of the tree are used for pharmacological actions. Experimental studies have demonstrated antiinflammatory, analgesic, hypoglycemic, laxative and antidiarrheal effects of black mulberry extract [13,14,18]. The aim of the current study was to determine whether M. nigra could improve pathological changes in the liver induced by CCl 4 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Almost all the parts of the tree are used for pharmacological actions. Experimental studies have demonstrated antiinflammatory, analgesic, hypoglycemic, laxative and antidiarrheal effects of black mulberry extract [13,14,18]. The aim of the current study was to determine whether M. nigra could improve pathological changes in the liver induced by CCl 4 .…”
Section: Discussionmentioning
confidence: 94%
“…Its berries are used in medicine against inflammation and to stop bleeding, the bark is used for toothache, and the leaves for treating snakebites and as an antidote to poisoning [12,13]. Another study showed that black mulberry possesses prokinetic, laxative and antidiarrheal effects, putatively mediated through cholinomimetic, antimuscarinic, and Ca 2+ antagonist mechanisms, respectively [14]. M. nigra is used in ethnomedicine for the prevention and treatment of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic extract produced from the dried fruit of Morus nigra at two different concentrations, 30 and 70 mg/kg, was used to test for laxative properties in BALB/c mice of both sexes. The functionality of the extract was evidenced by prokinetic and laxative activities, possibly mediated by the stimulation of muscarinic receptors through a combination of the Ca 2+ channel blocks and anticholinergic effects [39].…”
Section: Therapeutic Use Of the Species Morusmentioning
confidence: 99%
“…Atropine, a classic anti-cholinergic agent, could inhibit intestinal peristalsis, slow down gastrointestinal transit, contract arteriole in intestinal mucosa, and thus reduces secretion and defecation [25, 26]. As reported, atropine was applied to induce constipation in murine model, mimicking clinical constipation [27].…”
Section: Methodsmentioning
confidence: 99%